Analysis of fracture mechanics and fatigue crack growth in moderately thick plates using an efficient meshfree approach. (June 2021) - Mohammadi Anaei, M.T.; Khosravifard, A.; Bui, T.Q.
Highlights: We present an efficient meshfree method for analysis of fracture in plates under bending. Fatigue crack growth in cracked plates is numerically investigated under combined loading. Advantages provided as moment and stress intensity factors are computed with minimal labor. Using the BDM, the discontinuity of the domain and shape functions is captured accurately. The developed approach is less sensitive to distribution of the nodal points. Abstract: This paper presents a robust meshfree technique for computation of moment and stress intensity factors, and analysis of fatigue crack growth in cracked plates under the application of in- and out of-plane loads; a methodology for efficient and accurate computation of parameters of fracture mechanics problems is thus developed. Although having small computational labor and few complications of formulation, the proposed method has a high accuracy and convergence rate. By adding a few nodes in the vicinity of the crack tip, instead of enriching the basis functions, the singularity of the crack-tip fields is well captured with high accuracy. Also, by employing the background decomposition method (BDM), which is an efficient method for evaluation of the domain integrals, accurate solutions are obtained with small computational labor. The stress and moment intensity factors, which are two major parameters in analysis of the crack behavior, and prediction of its growth path, are calculated using the domain form of the interaction integral. Fracture mechanics problems under static condition, as well as under fatigue condition are investigated. Applying the meshfree radial point interpolation method along with the BDM has led to not only accurate results but also small computational cost. The accuracy of the results achieved for the stress intensity factors and also fatigue life of cracked bodies under cyclic loading is assessed by comparing the computed results with those found in the literature.